The Effect of Special Exercises Using Fast Play for Developing Tactical Performance By Changing Direction and Scoring In Young Soccer Players Aged 14 – 16 years Old - Hussein, Raad; Salam, Mustafa (Journal of Physical Education, 2019)
The Effect of Special Exercises Using Fast Play for Developing Tactical Performance By Changing Direction and Scoring In Young Soccer Players Aged 14 – 16 years OldThe problem of research lies in most of Iraqi players has a good performance during the exercise while not performing the same during the game. The research aimed at preparing special exercise for fast play to develop the cognitive side and behavior of tactics in soccer players aged 14-16 years old as well as identifying the effect of exercise in fast tactics on the development of knowledge and tactics behavior of the players. The hypothesis of the research was there are statistical significance differences between pre and posttests of the experimental and control groups in favor of posttests. In addition to that there are statistically significant differences in posttests between experimental and control groups. The researcher used the experimental method. The subjects were 20 players. The researchers concluded that the cognitive side has played a major role in the success of offensive style in selecting appropriate solutions in offensive game situations as well as quick play exercises have a positive effect in the development of the players. Finally the researcher recommended designing exercises for quick play to develop the cognitive and behavior of the players in different age groups. In addition to that, he emphasized the importance of fast play exercises during the period of special preparation because of the importance in developing the knowledge of the players.Keywords: fast play, soccer, tactics, young player.